Free Will as An Epistemically Innocent False Belief - Fabio Tollon (European Journal of Analytic Philosophy, 2023)
In this paper I aim to establish that our belief in free will is epistemically innocent. Many contemporary accounts that deal with the potential “illusion” of freedom seek to describe the pragmatic benefits of belief in free will, such as how it facilitates or grounds our notions of moral responsibility or basic desert. While these proposals have their place (and use), I will not explicitly engage with them. I aim to establish that our false belief in free will is an epistemically innocent belief. I will endeavour to show that if we carefully consider the circumstances in which particular beliefs (such as our belief in free will) are adopted, we can come to better appreciate not just their psychological but also their epistemic benefits. The implications, therefore, for future investigations into the philosophy of free will are that we should consider whether we have been too narrow in our pragmatic defences of free will, and that we should also be sensitive to epistemic considerations.